The impact of the absence of an internal audit function /department in the judicial service commission: a case study of Bulawayo high court - Ncube, Yedwa (Midlands State University, 2017)
The purpose of this project is to assess the impact of the absence of an internal audit function / department and related performance of Judicial Service Commission. While empirical works have given diverse reasons for the poor financial performance of the Commission , research evidences the impact of the absence of internal audit practices on the financial performance of Judicial Service Commission in a case study of Bulawayo High Court in context .Chapter 1 0f the research project highlights shortly the purpose of the study , as well as the approach taken by the researcher taken to address the problem .Chapter 2 reviews the available literature on the effects and impact of the absence of an internal audit function / department in the Judicial Service Commission – A case study of Bulawayo High Court .Chapter 3 details the research methodology . It shows the type of research carried out and the field work conducted by the researcher. Chapter 4 summarizes the Findings from the researcher `s observation , and analyses the responses from questionnaires .Chapter 5 concludes the whole research project and suggests some recommendations on the need to install and implement the internal audit function / department and the associated benefits .